Birth mode is associated with earliest strain-conferred gut microbiome functions and immunostimulatory potential - Linda Wampach (Nature Portfolio, 2018)
The effects of caesarean section delivery on mother-to-neonate transmission of microbiota are unclear. Here the authors show that caesarean section delivery can affect the transmission of specific microbial strains and the immunomodulatory potential of the microbiota.